2005
DOI: 10.5144/0256-4947.2005.313
|View full text |Cite
|
Sign up to set email alerts
|

Drug-resistant pulmonary tuberculosis in western Turkey: prevalence, clinical characteristics and treatment outcome

Abstract: BACKGROUNDAlthough high antituberculosis (anti-TB) drug resistance rates have been reported in Turkey, the clinical characteristics and implications for the outcome of anti-TB treatment have not been fully investigated. We determined the prevalence of anti-TB drug resistance and examined demographic data, clinical characteristics and treatment outcome in relation to patterns of resistance.METHODSFrom the TB case registry of a university hospital and the two largest dispensaries in Manisa city, we identified al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
2
15
3
Order By: Relevance
“…The rate of resistance to any drug (28.7%) found in this study is 7.6 to 9.7% higher than previously reported in Turkey and approximately 9% higher than the WHO 2008 global estimate (20,25,26,28). The MDR rate (4.5%) found in the current study is slightly lower than the estimated 5.3% global prevalence (28).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The rate of resistance to any drug (28.7%) found in this study is 7.6 to 9.7% higher than previously reported in Turkey and approximately 9% higher than the WHO 2008 global estimate (20,25,26,28). The MDR rate (4.5%) found in the current study is slightly lower than the estimated 5.3% global prevalence (28).…”
Section: Discussioncontrasting
confidence: 50%
“…Although the TB incidence in Turkey has decreased by half since 1985, several studies have shown the proportion of drugresistant TB cases to be higher than the global average (3,5,10,11,20,24,26). In 2005, Surucuoglu and colleagues reported that the rate of resistance to any anti-TB drugs among 355 isolates of Mycobacterium tuberculosis obtained from western Turkey was 21.1%, while another study found that among the 1,513 TB cases diagnosed in Istanbul, Turkey, in 2005, 19% were resistant to at least one drug (20,25). These rates are similar to the rates of drug resistance found in some of the Eastern European countries that are considered to have the highest drug resistance rates in the world (3).…”
mentioning
confidence: 99%
“…Also, in a recent survey, 41 (16.3%) of 252 M. tuberculosis isolates collected from the patients of different parts of Iran, including five provinces, were resistant to at least one anti-tuberculosis drugs (40). This study indicated lower drug resistance rates in Iran than the studies conducted in Turkey, Iraq, and Pakistan with the drug resistance rates of 21.1%, 29.7%, and 64% respectively (15,60). Recently, M. tuberculosis strains that are Extra-drug-resistant, i.e.…”
Section: Multidrug-resistant Tuberculosis In Irancontrasting
confidence: 46%
“…Although drug resistance surveillance has not been performed at the national level in Turkey, MDR TB reportedly varied in a range from 1.3 to 4.8% for initial drug resistance and from 4.4 to 16.6% for acquired drug resistance in local studies (5,8,31,32). Globally, any drug resistance and MDR rates ranged from 16 to 24% and from 4.8 to 7.3%, respectively (19,24,30). The frequencies of primary and secondary resistance to a single drug varied from 18 to 26.6% and from 28 to 53.4%, respectively (5,31,32,36).…”
Section: Discussionmentioning
confidence: 99%